Sentiment Analysis of The Constitutional Court Decision Regarding Changes to The Age Limit for Presidentian and Vice Presidential Candidates Using Support Vector Machine - Abilya Amanda; Nonong Amalita; Dodi Vionanda; Zilrahmi (UNP Journal of Statistics and Data Science, 2024)
The Constitutional Court (MK) as a judicial institution granted a judicial review on October 16, 2023 related to the Election Law Article 169 (q) Law No.7 of 2017 number 90/PUU-XXI/2023. The Constitutional Court approved the material test, leading to changes in the age limit for presidential and vice presidential candidates. This change caused controversy because it was considered to benefit one of the candidate pairs. This research aims to see the trend of public opinion towards policy changes by the government. This research uses the Support Vector Machine (SVM) method which divides the data into two classification classes. The application of linear, Radial Bias Function (RBF), and polynomial kernels resulted in the highest accuracy of 84%. The calculation of accuracy, precision, and recall is 84%, 22%, and 90%, respectively. Based on the resulting wordcloud, Positive words indicate backing for presidential and vice presidential candidates. Meanwhile, negative sentiments express disapproval of the Constitutional Court's decision concerning the changes to the age limit requirements for presidential and vice presidential candidates.